2013
DOI: 10.1159/000354459
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Hydrogen-Rich Solution on Aplastic Anemia in Vivo

Abstract: Background: Aplasitc anemia (AA) is a bone marrow failure syndrome characterized by an immune-mediated destruction of hematopoietic stem cells. Though clinical symptoms could be ameliorated by bone marrow transplantation and/or immunosuppressive therapy, frequent recurrence and especially evolution of clonal hematologic diseases remains problematic clinically. Cytokines such as interferon-γ (INF-γ), tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) secreted by autologous T cells are closely related with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Caudal vein WBC was counted in cell count plate at the same time of the day as described previously [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Caudal vein WBC was counted in cell count plate at the same time of the day as described previously [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Combination therapy with H 2 and hyperoxia or HS treatment provides enhanced therapeutic efficacy via both anti-oxidative and anti-inflammatory mechanisms, and might be a clinically feasible approach to treat sepsis [ 228 231 ]. Other studies indicated that H 2 administration accelerated recovery in aplastic anemia mice [ 232 ], increased blood alkalinity in physically active men [ 233 , 234 ], inhibited collagen-induced platelet aggregation in healthy humans and rats [ 235 ], and elevated serum anti-oxidative function in thoroughbred horses [ 236 ].…”
Section: Preventive and Therapeutic Applications Of Hmentioning
confidence: 99%
“…TNF-a, IFN-g and IL-6 in serum decreased after the application of H2-rich solution [96]. Zhai et al [97] reported that brucine can reduce the levels of TNF-a and IFN-g through inhibiting the proliferation of T lymphocytes in AA patients.…”
Section: Five-year Viewmentioning
confidence: 99%